Status of Robots in Moral and Legal Systems - Ginszt, Katarzyna (ETHICS IN PROGRESS, 2019)
David J. Gunkel in his latest book Robot Rights presents the opportunities and challenges of integrating robots into moral and legal systems. The research question asked by the author is “Can and should robots have rights”? Following the Humean distinction between “is” and “ought”, Gunkel creates four statements that either opt for or against incorporating robots into legal discourse. The four modalities group contrasting opinions developed by different scholars on the subject of the eponymous robot rights. The author provides readers with yet another alternative approach to the question of legal recognition of robots which is based on Levinasian philosophy.